Intervenções mediadas por pares aplicadas a crianças com TEA para promover interação social em ambientes escolares: análise com base em publicações - Vieira, Mariana Cavalcante (2018)
Peer mediated interventions are used to increase social interactions of children in the Autistic Spectrum Disorder (ASD) with their peers by building the behavioral repertoire of the peers to act as intervention agents. Peer mediated interventions are considered the most empirically valid type of intervention for children with ASD and the best to increase social interactions between those children and their typically developing peers. However, those interventions are reaching inconsistent results in tests of generalization and maintenance of behaviors. The aim of the present study was to analyze the objectives, the methodological characteristics, the results, and the relation between some of the methodological characteristics and between those characteristics and the results of experimental researches about peer mediated interventions that had data of social interaction in the school settings. Forty-one studies were selected from three data bases (CAPES, PsycINFO e Science Direct), in the list of two reviews in the area - Chan et al. (2009) e Watkins et al. (2015) – and in the personal files of the researcher. Sixty-four variables were analyzed, organized in 15 groups: objectives, ASD participants, behavioral repertoire of the participants with ASD, peers, settings, strategies, training, tests, VD, measured behaviors, maintenance, generalization, social validity, integrity and results. The results were, in general, positive, although few studies contained integrity, social validity and maintenance tests. Inconsistencies in the results of the maintenance tests and the generalization tests were found. Studies that used Prompt and reinforce had better results than the ones that used Peer-initiation intervention. More research is needed in order to assure if the peer mediated interventions are reinforcement contingencies that really promotes increase of social interaction with peers